REFLECTIVE PRACTICE AS A PEDAGOGICAL CONDITION FOR DEVELOPING METACOMPETENCE IN FUTURE PRIMARY (International Conference on Education, Psychology and Humanities, 2026)
The article discusses the role of reflective practice in developing the metacompetence of future primary school teachers. In modern teacher education, professional preparation is not limited to the acquisition of subject knowledge and methodological skills. It also requires the ability to analyse one’s own pedagogical actions, regulate learning strategies, make independent decisions and adapt to changing educational contexts. The paper is based on theoretical analysis, comparative pedagogical interpretation and generalisation of recent international studies on self-regulated learning, reflective practice, Lesson Study, digital competence and research competence in teacher education. It is argued that reflective practice acts as a central pedagogical mechanism through which future teachers become able to connect theoretical knowledge with real classroom situations. The paper also outlines practical directions for integrating reflective tasks, case analysis, project-based learning and digital tools into the preparation of future primary school teachers. The findings may be used to improve methodological training in pedagogical higher education institutions.
Keywords: Metacompetence, reflective practice, primary education, future teachers, self-regulated learning, teacher education.